Dutt, V.P., India's Foreign Policy, Vikas Publishing House PVT LTD, Delhi, 1984, x + 448 pp. - Miguel S. Wionczek (El Colegio de México, A.C., 1985)
Kumar, Satish (editor), Yearbook on India's Foreign Policy, 1982-83, Sage Publications, New Delhi-Beverly Hills-London, 1985, 266 pp.